Ιεροί Κανόνες και Ιεράρχηση της Ζωής και Υγείας (Holy Canons and Hierarchy of Human Life and Health, 2020)
Restrictions on exercising worship can be applied for the protection of hunan life  and health during pandemic crisis  by the power of the 88th Canon of the Penthekti Ecumenical Synods (In Trullo, 691).The Holy Canon introduces a  general principle within the postitive law of the Church. It is described as the principle of apatheia:  "And we are taught that the Sabbath was made for man: wherefore also the safety and comfort of man are by all means to be placed first."